Implementation of the Duties and Functions of the Aviation Accident Relief and Fire Fighting Unit at UPBU nggul Wulung Cilacap - Fauzi, Rizki Ahmad; Kurniasari, Zenita (CV. Rayyan Dwi Bharata, 2023)
Indonesian aviation still faces safety problems. The reputation of Indonesia's air transportation system has been damaged by a number of aviation accidents. Human error is a component that can cause plane crashes. These human factors will be explained in the following explanation: smoke from burning dry leaves by local residents in the Apron area and the level of alertness of the Aviation Accident Relief and Fire Fighting Unit (PKP-PK) at ANGKAL Wulung Airport, Cilacap. Based on several existing problems, the aim of this research is to find out how human error can cause plane crashes. This type of research is qualitative and descriptive. By using qualitative research methods, the author's aim is to display and reveal the information and symptoms discussed in this research. In particular, the author will analyze and explain the main tasks and functions of the Aviation Accident Relief and Fire Fighting Unit (PKP-PK) at UPBU nggul Wulung Cilacap. Interviews, observation, and documentation are the data collection methods used in this research. The results of the research show that the PKP-PK unit at nggul Wulung Cilacap Airport carries out personnel duties and functions in accordance with what is stipulated in PR 30 of 2022 concerning Technical Standards and Operations of Civil Aviation Safety Regulations Part 139, which states that the duties and functions of PKP-PK are saving lives and property from aircraft that experience incidents or accidents, as well as preventing, controlling and extinguishing fires. The obstacle faced by PKP-PK personnel is regarding the storage building for extinguishing equipment and materials. There is also a solution to the obstacles faced by PKP-PK personnel, namely the construction of storage dams for equipment and extinguishing materials.